Estimating the Cost of Point-of-Care Early Infant Diagnosis in a Program Setting: A Case Study Using Abbott m-PIMA and Cepheid GeneXpert IV in Zimbabwe. (1st July 2020) - Mukherjee, Sushant; Cohn, Jennifer; Ciaranello, Andrea L.; Sacks, Emma; Adetunji, Oluwarantimi; Chadambuka, Addmore; Mafaune, Haurovi; Makayi, McMillan; McCann, Nicole; Turunga, Esther
Abstract : Background: Point-of-care early infant diagnosis (POC EID) increases access to HIV test results and shortens time to result-return and antiretroviral therapy initiation, as compared to central laboratory-based EID. However, to scale-up POC EID, governments need more information about programmatic costs. Methods: We evaluated POC EID costs from a health systems perspective. Our primary analysis assessed the Abbott m-PIMA and 2 versions of the Cepheid GeneXpert IV platforms—with a solar battery or gel battery—used in Zimbabwe, with instrument purchase. We also included the following 2 scenarios with zero upfront equipment purchase: (1) m-PIMA using a reagent rental model, with an all-inclusive price when the buyer commits to an average testing volume, and (2) GeneXpert IV, reflecting contexts where GeneXpert is already in place for tuberculosis diagnosis or HIV viral load monitoring. We collected data from project expenditures, observations of health workers, and from government salary scales. We calculated cost per EID test based on number of EID tests performed on each machine per day. Results: The cost per successfully completed test was 44.55 for m-PIMA with platform purchase and 25.89 for m-PIMA reagent rental. Costs for GeneXpert IV with platform purchase were 25.70 using a solar battery, 25.29 using a gel battery, and 23.85 under a scenario assuming no equipment costs. In our primary analyses, materials costs comprised 73%–74% total costs, equipment 14%–20%, labor 5%–8%, training 1%, facility upgrades 1%, and monitoring 1%. Conclusions: As countries consider scaling up POC EID, these data are important for budgeting and planning.